Função paterna e sociabilidade violenta em jovens escolares - Ferreira, Antônio Eustáquio (2012)
The pillar that supports this thesis consisted of psychoanalysis in critical social situations, using these instruments: semi-structured interviews for study 1 and a focal group for study 2. We undertook a Discourse Analysis as developed by Pêcheux (1983), Minayo (2000) and Orlandi (2005), as well as the investigation of the modal verbs can , want to, should and have to/need to , in their different modes, identifying how these verbs, as used by the respondents, relate to epistemic or deontic modalities, pursuant to Santos (1999), Santos (2000), Alves (2007) and Martins (2011). The main objective of this study was to establish a reflection on the means through which the transformations that have taken place within the family and the decline of patriarchy can have influenced the so-called decline of the paternal function , in its most traditional meaning. Analyze the aspects related to emerging concept of childhood and adolescence, the society of narcissism, how they contributed to the decline of the father , and how they influenced the decline of the paternal function and provided subsidies to violence in social interaction of young students. Specifically, the aim of this thesis was to obtain information on actions categorized as violent by young students; identify factors that contribute to school violence among young people and determine the relationship between violent sociability in young students and the paternal function. As a result, it is possible to conclude that children and young people were gradually subjected to the condition of subjects. However, changes that have been taking place in the family and in how its members are dealt with, mainly the children and the young people, have altered the relationship between parents and their children. New social actors and the State interfere in family life, by occupying the place of a symbolic father, replacing parents in their duties and weakening the authority of the father and his function. Therefore, this study leads us to the assumption that it is violence, taken as a producer of meanings that guides the current violent sociability among young students, resulting from the decline of the paternal function.